Innovating the Piriang Diateh Karambia Dance as a Cultural Tourism Asset in the Solok City - Wimbrayardi, Wimbrayardi; Putra, Irdhan Epria Darma; Rosalina, Venny (Universitas Negeri Medan, 2023)
The potential of local culture, namely Piriang Diateh Karambia Dance in tourism development, is part of a product of human creativity that has economic value. This innovative goal is to analyze local culture as a cultural tourism attraction in Solok City which is packaged in the form of performances. Piriang Diateh Karambia dance is in the tourist bag in Solok City. This service method used is qualitative analysis through direct observation and indepth interviews with related parties. To analyze the potential and problems in the local culture of Piariang Diateh Karambia Dance as a cultural tourism attraction at the location where Piriang Diateh Krambia Dance grows including internal and external potential and problems. Local culture of Piriang Diateh Karambia Dance, especially in Solok City in general, has unique potential and art product centers need to be innovative as a means of performing arts that can increase cultural tourism. Innovative strategies as an increase in the local culture of Piariang Diateh Karambia Dance will attract tourists who come to the cultural bag in Solok City. Innovative local culture of Piriang Diateh Karambia Dance in Solok City, made into attractive packaging as a performing art to come to Solok City. Besides being presented as a performing art that will stimulate community economic growth through UMKM in natural tourism pockets in Solok City.